Bacterial Diversity in Biological Soil Crusts from Extrazonal Mountain Dry Steppes in Northern Mongolia - Kemmling, Anne; Pfeiffer, Birgit; Daniel, Rolf; Hoppert, Michael (DigitalCommons@University of Nebraska - Lincoln, 2012)
Biological Soil Crusts (BSCs), consisting of prokaryotes, microalgae, lichens, mosses and eventually small vascular plants, cover wide areas in arid and semi-arid environments. In the present study, the microbial diversity of these crusts was explored at extrazonal mountain steppe sites in the western Khentej (Northern Mongolia). At the study site the Siberian taiga borders on the Mongolian-Daurian forest steppe, resulting in a unique intermixture of the dark taiga, the light taiga, and forest steppe (DULAMSUREN 2004). Due to the presence of boreal, temperate and dauric elements the forest steppe is eminently rich in species (MÜHLENBERG et al. 2004). BSCs in the western Khentej only occur in mainly non-forest areas of the Carex amgunensis-, Festuca lenensis-, Pulsatilla ambigua- and Artemisia frigida-mountain-dry-steppe and Ulmus pumila-open woodland (DULAMSUREN 2004). BSCs at these sites contain small vascular plants, mosses, lichens, and different microorganisms in varying ratios. In this communication, the diversity of BSCs, especially with respect to bacterial phylotypes in two different sites with a diverging degree of disturbance is presented. According to results based on 16S rDNA analysis, the relative abundance of Cyanobacteria decreases on disturbed sites, whereas abundances of other large groups increase. Generally, the more disturbed site appears to be more diverse.